IMPACT OF BUSINESS PROCESS AUTOMATION ON THE ORGANIZATION AND PERFORMANCE RESULTS OF ENTERPRISES - DYKHA, Mariia; KOLISNICHENKO, Paulina; BODNAR, Ivanna; KRYVENCHUK, Yelyzaveta (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates that business process automation is a progressive form of organizing the activities of enterprises. It provides qualitative changes in the functioning of enterprises, manifesting itself at the operational, tactical and strategic levels of management. Modern business process automation tools are studied: Enterprise Resource Planning, Customer Relationship Management, Business Process Management, Robotic Process Automation, IA, Low-code / No-code platforms, Cloud solutions for automation. Their characteristics, advantages, limitations of use. Among the advantages of automation tools, the following are identified in particular: data centralization; increased planning accuracy; processing of unstructured data; reduced duplication of information; increased transparency and flexibility of operations; flexibility in configuration; reduced manual labor costs; scalability; lower infrastructure costs; accessibility from any location. The following are identified as limitations of business process automation: implementation cost; long adaptation period and level of digital literacy of personnel; the need for large-scale process changes; the need for careful tuning; dependence on the quality of data entry; limited benefit without integration with other systems; works only with regulated, stable processes; risk of creating "shadow" IT solutions; cybersecurity issues. The feasibility of implementing business process automation in various industries / areas of activity (in production, logistics, banking, e-commerce, document processing, etc.) is described, depending on the characteristics of the relevant automation tools. The main results of the implementation of automation tools are substantiated: increased labor productivity and optimization of operational processes; reduction of the impact of the human factor and increased reliability of business processes; improved quality of management decisions and data accuracy; transparency of management and the possibility of real-time monitoring; financial and economic effects (reduction of direct operating costs due to automation of manual operations; reduction of time costs, which increases resource turnover; increased accuracy of planning and budgeting, which contributes to better use of financial resources; improved quality of interaction with customers, which leads to increased sales and increased loyalty); organizational effects and changes in corporate culture.